PENERAPAN METODE SAW DALAM SISTEM PENDUKUNG KEPUTUSAN PERPANJANGAN KONTRAK THL (TENAGA HARIAN LEPAS) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SIBOLGA - Natanael, Anju Mastaurat; Fahmi, Hasanul (Jurnal Sistem Informasi Kaputama (JSIK), 2022)
The Population and Civil Registration Office of the City of Sibolga provides an extension of the freelance daily labor contract (THL) which is carried out once a year. However, with the many proposals and the many criteria used in the assessment, this makes it difficult for the Dinas to make a decision about who is entitled to apply for an extension of the work contract. The solution to the problem of extending the contract for casual daily workers at the Department of Population and Civil Registration of Sibolga City is by making a decision support system for extending the contract for casual daily workers using the SAW method. The SAW (Simple Additive Weighting) method was chosen because this method determines the weight value for each attribute, then continues with ranking which will select the best alternative from a number of alternatives.